Rhythmic swaying induced by sound in chimpanzees (Pan troglodytes) - Hattori, Yuko (Proc Natl Acad Sci U S A, 2020)
Music and dance are universal across human culture and have an ancient history. One characteristic of music is its strong influence on movement. For example, an auditory beat induces rhythmic movement with positive emotions in humans from early developmental stages. In this study, we investigated if sound induced spontaneous rhythmic movement in chimpanzees. Three experiments showed that: 1) an auditory beat induced rhythmic swaying and other rhythmic movements, with larger responses from male chimpanzees than female chimpanzees; 2) random beat as well as regular beat induced rhythmic swaying and beat tempo affected movement periodicity in a chimpanzee in a bipedal posture; and 3) a chimpanzee showed close proximity to the sound source while hearing auditory stimuli. The finding that male chimpanzees showed a larger response to sound than female chimpanzees was consistent with previous literature about “rain dances” in the wild, where male chimpanzees engage in rhythmic displays when hearing the sound of rain starting. The fact that rhythmic swaying was induced regardless of beat regularity may be a critical difference from humans, and a further study should reveal the physiological properties of sound that induce rhythmic movements in chimpanzees. These results suggest some biological foundation for dancing existed in the common ancestor of humans and chimpanzees ∼6 million years ago. As such, this study supports the evolutionary origins of musicality.